Implementation of the federal project "Development of export of medical services" in the pre-COVID period - G. D. Petrova (Здоровье мегаполиса, 2022)
Introduction. The relevance of the problem under study is due to the fact that the medical services market, like any market structure, is regulated on the basis of competition among the involved medical organizations, the interaction of supply and demand, free pricing for various nosologies in the process of selling services. The medical services market has a unique specificity: high dynamism of all processes, relatively fast capital turnover, susceptibility to changes in market conditions, a high level of differentiation of services, and unclear outcomes. In addition, in the conditions of external sanctions pressure, the priority direction of the domestic economy is the development of non-commodity exports, in particular, the export of services, which includes the export of medical services. Since 2022, the Russian Government has been paying special attention to this area.The purpose of the study: to analyze the activities of eight federal districts in the pre-crisis period, contributing to the development of the export of medical services and to identify the leading federal districts that make the greatest contribution to the development of the export of medical services.Results and conclusion. The results of the study of eight federal districts of the Russian Federation in the doskovid period showed the process of formation of exports of medical services, the number of treated foreign citizens in these districts, earned income in millions of US dollars. The Central, Ural, and Northwestern Federal Districts are leading in this process, which is the current model for the rest of the federal districts.The study demonstrates the work of federal districts – in numbers, percentages, monetary terms in conventional units. Also presented are indicators indicating an increase in the volume of exports of medical services by at least 4 times compared to 2017, which amounted to an income of 128.38 million US dollars for 2019.